ANALISIS KEPEMILIKAN MANAGERIAL BERBASIS PADA TEORI KEAGENAN - OCTALIANNA OCTALIANNA; DEASY ARIYANTI RAHAYUNINGSIH (Jurnal Bisnis dan Akuntansi, 2013)
The purpose of this study is to examinethe influence of debt policy, company performance, company value, dividend policy, earnings volatility and investment against managerial ownership.This study uses an agency theory as a based to do the reasearch. This research used data were taken from all companies listed in Indonesia Stock Exchange over the three years period 2009-2011. This research uses purposive sampling method. The sample of this research consists of 47 companies. The hypotheses proposed were tested by binary logistic regression. The result shows that debt policy, company performance, company value, dividend policy, earnings volatility and investment have no influence to managerial ownership.